Human Serum With High Neutralizing Antibody Titers Against Both Zika and Dengue Virus Shows Delayed In Vitro Antibody-Dependent Enhancement of Dengue Virus Infection - Valiant, William G (Open Forum Infect Dis, 2018)
Zika virus infection in a dengue virus–naïve subject was associated with the induction of high levels of cross-reactive binding antibodies. These responses were, however, largely non-neutralizing and displayed a capacity to enhance dengue infection in vitro at significantly low dilution (1:10). In contrast, a subject who had high levels of neutralizing antibodies against both dengue and Zika viruses enhanced infection at a dilution of 1:10 000. These results suggest that high levels of dengue cross-neutralizing antibodies could potentially prevent the enhancement of dengue infection in Zika virus–convalescent individuals.